Effects of initial defects on strain measurement and elastic modulus of 3D-printed CFRP - Keisuke IIZUKA; Takumi ITO; Satoru YONEYAMA (Mechanical Engineering Journal, 2024)
The effects of initial defects, such as fiber breakage, on the strain measurement of 3D-printed carbon fiber-reinforced plastic (CFRP) are evaluated herein. The generation of defects is difficult to avoid during the 3D printing process of CFRP, resulting in degradation of the tensile strength. However, the effects of these initial defects on the elastic modulus have not been investigated. The elastic modulus is generally determined by performing strain measurements using strain gauges and extensometers, as defined by testing standards. Strain gauges and extensometers are attached to the specimen, and therefore, the measurement is affected by the specimen surface, which contains initial defects. In this study, the effects of initial defects on the strain measurement are examined by performing tensile tests, evaluating the elastic modulus, and comparing the results of the 3D-printed CFRP with those of a homogeneous material, namely aluminum. The elastic modulus is evaluated using strain gauges, extensometers, and digital image correlation (DIC). The strain in homogeneous materials is independent of the strain gauge position, but strain variation is observed in CFRP depending on the position, presumably owing to the defect distribution. Furthermore, the strain obtained from extensometers with longer gauge lengths is also affected by the initial defects. Moreover, the variation is larger for the strain obtained by DIC than that obtained using strain gauges or extensometers. The strain distribution obtained by DIC may be useful for identifying the positions where the effects of initial defects are significant.